Electric Vehicle Modelling for Future Technology and Market Penetration Analysis - Bin Ahmad, Muhammad Salman; Pesyridis, Apostolos; Sphicas, Panos; Mahmoudzadeh Andwari, Amin; Gharehghani, Ayat; Vaglieco, Bianca Maria (Frontiers in Mechanical Engineering, 2022)
The transportation sector is generally thought to be contributing up to 25% of all greenhouse gases (GHG) emissions globally. Hence, reducing the usage of fossil fuels by the introduction of electrified powertrain technologies such as hybrid electric vehicle (HEV), battery electric vehicle (BEV) and fuel cell electric vehicles (FCEV) is perceived as a way towards a more sustainable future. With a seemingly more significant shift towards BEV development and roll-out, the research and development of BEV technologies has taken on increasing importance in improving BEV performance and ensuring its competitiveness. Numerical simulation, using MATLAB, is performed as a tool to investigate and to improve the overall performance of BEVs. This study provides an overview of the possible technology outcome and market consequences for future compact BEVs along with HEVs, FCEVs and internal combustion engine vehicles (ICEV). The techno-economics of BEVs, market projection and cost analysis up to 2050 are investigated, together with detailed of BEVs alongside other types of vehicles are discussed. Well-to-wheel analysis of BEVs is also studied and compared with HEV, FCEV and ICE.